The Spirituality of Contemporary Danes – between Paganism and Secularisation - Katarzyna Krawerenda-Wajda (Ksiegarnia Akademicka Publishing, 2019)
The topic of the article is the issue of the place of religion in contemporary Danish society. Not only Scandinavia, but all of Europe is subject to secularisation processes. As a result of this process, the role of the Christian religion remains limited or eliminated. However this crisis of religion, does not affect the deeprooted desire for transcendence and individual search for it. In the case of Denmark, it appears in a return to neo-paganism – a reconstructionist religion that attempts to return to the religion of the “nature” of ancient and early medieval Germans. An example of this religion is the Ásatrú movement, dynamically developing in Denmark. On the other hand, the need for transcendence is realised by the phenomenon of spirituality, which is the need for self-transcending. Both of these directions are an expression of freedom, finding meaning, but also a conscious search for identity in a dynamically changing Europe.